Elaborasi Kompetensi Profesional Guru Kristen Sebagai Penguatan Karakter Anti Kekerasan di Sekolah Desa Tenalai - I Made Suardana; Jonathan Leobisa; Yakobus Adi Saingo; Yakob Pai Tiba; Korne Amelia Haba Ito (Universitas Muhammadiyah Malang, 2026)
Purpose – The aim of the PKM activity is to strengthen the professional competence of Christian teachers as agents of strengthening anti-violence character in schools in Tenalai Village, Landu Leko District, Rote Ndao Regency. Design/methodology/approach –The PKM activity used the Participatory Action Research (PAR) method, discussing the implementation of anti-violence values ​​with Christian teachers and other school staff. The collected data was then processed and analyzed reductively. Findings – The results of the Community Service Program activities show that Christian teachers at Tenalai Village School, Landu Leko District, Rote Ndao Regency who have mastered professional competencies are required to: (1) Design lesson materials, manage, and evaluate learning that contains anti-violence values; (2) Be able to apply science and technology in learning to strengthen anti-violence characters; (3) Be able to develop interactive learning skills to make every member of the school aware of the benefits of realizing an anti-violence character. Living these three indicators as an approach that is able to strengthen an anti-violence character, which is useful in providing a sense of security, comfort, order, justice, solidarity, and love in carrying out various activities. Originality/value – The implications and novelty of this PKM activity is to open the horizons of Christian teachers that mastery of professional competencies is not only limited to the theoretical realm for strengthening anti-violence character, but professionally can collaborate with various human resources in the school environment, in order to disseminate anti-violence character education in schools.